Peranan Penyuluhan dalam Pengembangan Usahatani Padi Hibrida di Subak Tegenungan, Desa Kemenuh, Kecamatan Sukawati, Kabupaten Gianyar - ADNYANA, I NENGAH SURATA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p41, 2022)
The Role of Counseling in the Development of Hybrid Rice Farming in Subak Tegenungan, Kemenuh Village, Sukawati District, Gianyar Regency Rice plant is the main commodity for Indonesia. The development below is still experiencing several obstacles and problems at the level of field farmers. For this reason, more innovative and creative solutions are needed to increase yield productivity.This research took place in Tegenungan Subak, Kemenuh Village, Sukawati District, Gianyar Regency. The location selection was chosen  purposively . The population is 43 people and the research sample is taken by  simple random sampling  as much as 40% of the total population, namely 18 hybrid rice farmers. Research data were analyzed qualitatively and quantitatively.The objektives of this study were (1) to analyze the role of Field Agricultural Extension in the development of hybrid rice farming in Subak Tegenungan, Kemenuh Village, Sukawati District, Gianyar Regency; (2) analyzing the role of the farming subsystem in the development of hybrid rice in Subak Tegenungan, Kemenuh Village, Sukawati District, Gianyar Regency; (3) analyzing the productivity of farming results in the development of hybrid rice in Subak Tegenungan, Kemenuh Village, Sukawati District, Gianyar Regency.The results showed that (1) the role of extension services in the development of hybrid rice farming in Subak Tegenungan, Kemenuh Village, Sukawati District, Gianyar Regency obtained an average score of 3.39 (67.91%) in the moderate category; (2) the hybrid rice development farming subsystem gets an average score of 3.07 or 61.48% in the medium category; (3) Grain yield productivity of hybrid rice reached 9.590 kg/ha which is classified as moderate.Suggestions that can be given are (1) Field Agricultural Extension which includes the use of visual aids, growing farmer enthusiasm, being able to provide and invite farmers to develop hybrid rice farming needs to be improved again; (2) the farming subsystem in the development of hybrid rice, the things that need to be improved are rotating varieties, plowing the soil twice, draining the seeds and incubating them for 2 X 24 hours. This needs to be improved by hybrid rice farmers.